The role of legal acts in improving the legal regulation of educational activities - Kovalenko, MSc. Natalia E.; Kovalenko, Ph. D. Kseniya E.; Gribanov, Ph. D. Dmitry V. (Revista Conrado, 2018)
The state of the educational legislation predetermines the need to improve the quality of its content and the effectiveness of the action. Analysis of world practice shows that both excessive and inadequate regulation of social and economic processes negatively affects the economic development, social and political situation in the country, forming negative trends and low efficiency of state regulation. Various legal instruments are used to reduce the impact of these negative factors, one of which is the assessment of the regulatory impact. At present, the assessment of the regulatory impact is becoming an indispensable element of norm-setting. However, its application requires serious institutional and methodological support, the definition and formalization of the functions of participants and the procedures applied, which determines the feasibility of researching the theoretical foundations, practical experience and best practices for assessing regulatory impact. The purpose of the procedure is to develop an opinion on the achievement of the stated objectives of legal regulation in the process of the regulatory legal act, as well as to assess the positive and negative consequences of the regulatory legal act, and, possibly, the submission of proposals for the cancellation or amendment of a regulatory legal act or its individual provisions. Keywords: Education legislation, assessment of regulatory impact, legal consequences, defect of legislation, indicator of realizability. RESUMEN El estado de la legislación educativa predetermina la necesidad de mejorar la calidad de su contenido y la eficacia de la acción. El análisis de la práctica mundial muestra que tanto la regulación excesiva e inadecuada de los procesos sociales y económicos afecta negativamente el desarrollo económico, la situación social y política en el país, formando tendencias negativas y baja eficiencia de la regulación estatal. Varios instrumentos legales se utilizan para reducir el impacto de estos factores negativos, uno de los cuales es la evaluación del impacto regulatorio. En la actualidad, la evaluación del impacto regulatorio se está convirtiendo en un elemento indispensable del establecimiento de normas. Sin embargo, su aplicación requiere un apoyo institucional y metodológico serio, la definición y formalización de las funciones de los participantes y los procedimientos aplicados, lo que determina la viabilidad de investigar los fundamentos teóricos, la experiencia práctica y las mejores prácticas para evaluar el impacto regulatorio. El objetivo del procedimiento es desarrollar una opinión sobre el logro de los objetivos establecidos de regulación legal en el proceso de la ley reguladora, así como evaluar las consecuencias positivas y negativas del acto legal regulatorio y, posiblemente, la presentación de propuestas para la cancelación o modificación de un acto legal regulatorio o sus disposiciones individuales. Palabras clave: Legislación educativa, evaluación del impacto regulatorio, consecuencias legales, defecto de legislación, indicador de realizabilidad.